A36 HUMAN INTERLEUKIN-4 EDUCATED MACROPHAGES SUPPRESS DNBS-INDUCED COLITIS IN MICE. (15th March 2019) - Jayme, T S; Wang, A; Shute, A J; Beck, P; McKay, D M
Abstract: Background: We have shown that adoptive transfer of IL-4 stimulated alternatively activated macrophages (AAM) (i.e. M(IL4)) into wild-type mice can inhibit colitis. Mouse models of inflammation have shown that the AAM is important for wound healing: deletion of this type of macrophage can exacerbate disease by impairing wound repair. Translating this to humans, ongoing studies in our laboratory show that human M(IL4)s promote epithelial wound repair in vitro and this process is partially TGFβ dependent. Therefore, we tested the possibility that human M(IL4)s injected into Rag1 -/ - mice could suppress enteric inflammation. Aims: To assess the ability of human M(IL4)s to protect against DNBS-induced colitis in Rag1 -/ - mice. Methods: Human blood-derived macrophages from healthy volunteer donors were exposed to IL-4 (10 ng/ml; 48h) and expression of the M(IL4) markers CD206, CD14, CCL18 was assessed by qPCR. Human M(IL4)s (1x10 6 ) or mouse bone marrow-derived M(IL4)s (10 ng/ml; 48h; 1x10 6 ), as a positive control, were injected into male Rag1 -/ - mice (~8 weeks old) in 250 ml PBS ip., 48h before intra-rectal administration of DNBS (3mg in 100 ml 50% ethanol) to elicit colitis (100 ml PBS for controls). Necropsies were performed three days-post DNBS and disease assessed by measuring the colon and calculating macroscopic and histologic damage scores. Results: Macrophages from healthy donors responded to IL-4, converting to M(IL4)s as defined by increased mRNA for CD206 and CCL18 (and protein), and reduced CD14 mRNA. As before, murine M(IL4)s significantly blocked DNBS-induced colitis in Rag1 -/ - mice (Leung et al ., Mol. Med. 2016). Moreover, systemic delivery of human M(IL4)s from 7 of 8 donors resulted in significantly less severe DNBS-induced disease. Compared to DNBS-only treated mice, those given human M(IL4s) had longer colons, reduced macroscopic disease, lower levels of conA-stimulated TNFa production by splenocytes. While average colonic histopathology scores were lower in human M(IL4)-treated mice this was not a statistically different finding. Conclusions: Cellular immunotherapy has the potential to be a component of personalized medicine. Here using a semi-humanized mouse model of colitis we show that treatment with human M(IL4)s substantially reduces disease severity. These data are presented as proof-of-concept support for autologous M(IL4) transfer to treat IBD. Funding Agencies: CCCNSERC CREATE